School travel behaviors: How the pandemic impacted communities - Kevin Chang; Xinyi Li; Ahmed Abdel-Rahim (Transportation Research Interdisciplinary Perspectives)
The global pandemic in early 2020 significantly disrupted life for many families, and the trip to and from school was not immune to these disruptions. Parents and children alike made travel adjustments depending on their preferences with regard to personal health and safety, social distancing, and aversion to risk. Each school district and individual school also made decisions with regard to in-person or remote learning during this period of uncertainty.In this study, a research gap was filled by examining the effect of the pandemic on school transportation-related decisions for hundreds of families living in the United States. An online survey was developed and administered with the help of Qualtrics, an experience management company. Over 600 responses were gathered from across three Pacific Northwest states. In addition to collecting demographic data about the respondents, the survey asked about travel mode choices and characteristics of the trip to and from school. The collective results were then analyzed to determine which factors directly contributed to pandemic-related changes in travel behavior.The study concluded that parent education level, household income, and age of child were all statistically significant variables that affected behavioral change. Additionally, common travel assumptions associated with rural students, when compared with urban students, were confirmed. These factors included a greater reliance on a yellow school bus and lesser availability of critical infrastructure.